PERSEPSI MAHASISWA DALAM PEMBELAJARAN DARING PADA MATA KULIAH FARMASI SIMULASI DI MASA PANDEMI COVID-19 - Maryanti, Lilis; Rulianti, Mona Rahmi; Yuliani, Yuliani (Jurnal Riset Kefarmasian Indonesia, 2022)
This study aims to determine student perceptions of online learning in simulated pharmacy courses during the Covid-19 pandemic. This type of research is descriptive research. Sampling used a purposive sampling technique with clear inclusion criteria, namely students who had received a simulated pharmacy practice course in the fifth semester of the Pharmacy Department of the Health Polytechnic of the Ministry of Health of Palembang as many as 77 students. Questionnaires distributed via google form with a Likert-scale and one essay question. Analysis of the data is used by calculating the percentage of respondents and analyzing each indicator. The research results obtained are good perceptions from students of online learning in simulated pharmacy courses during the Covid-19 pandemic. The score for the percentage of respondents obtained for the teaching and learning process indicators shows good criteria of 72.7%, for lecturers' competence indicators showed good criteria of 79.2%, while for facilities and infrastructure indicators also showed good criteria of 75.1%